Electroacupuncture attenuates ferroptosis by promoting Nrf2 nuclear translocation and activating Nrf2/SLC7A11/GPX4 pathway in ischemic stroke - Xi-chen Yang; Ya-ju Jin; Rong Ning; Qiu-yue Mao; Peng-yue Zhang; Li Zhou; Cheng-cai Zhang; Yi-chen Peng; Na Chen (Chinese Medicine)
Abstract Objective Electroacupuncture has been shown to play a neuroprotective role following ischemic stroke, but the underlying mechanism remains poorly understood. Ferroptosis has been shown to play a key role in the injury process. In the present study, we wanted to explore whether electroacupuncture could inhibit ferroptosis by promoting nuclear factor erythroid-2-related factor 2 (Nrf2) nuclear translocation. Methods The ischemic stroke model was established by middle cerebral artery occlusion/reperfusion (MCAO/R) in adult rats. These rats have been randomly divided into the EA + MCAO/R group, the MCAO/R group, the EA + MCAO/R + Brusatol group (the inhibitor of Nrf2), and the EA + MCAO/R + DMSO group, and the Sham group. The EA + MCAO/R group, EA + MCAO/R + Brusatol group, and the EA + MCAO/R + DMSO group received EA intervention 24 h after modeling for 7 consecutive days. The behavioral function was evaluated by Neurologic severity score (NSS), Garcia score, Foot-fault Test, and Rotarod Test. The infarct volume was detected by TTC staining, and the neuronal damage was observed by Nissl staining. The levels of Fe2+, reactive oxygen species (ROS), superoxide dismutase (SOD), and malondialdehyde (MDA) were measured by ELISA. The immunofluorescence and Western blotting were used to detect the expression of Total Nrf2, p-Nrf2, Nuclear Nrf2, and Cytoplasmic Nrf2, and the essential ferroptosis proteins, including glutathione peroxidase 4 (GPX4), solute carrier family 7 member 11 (SLC7A11) and ferritin heavy chain 1 (FTH1). The mitochondria were observed by transmission electron microscopy (TEM). Results Electroacupuncture improved neurological deficits in rats model of MCAO/R, decreased the brain infarct volume, alleviated neuronal damage, inhibited the Fe2+, ROS, and MDA accumulation, increased SOD levels, increased the expression of GPX4, SLC7A11 and FTH1, and rescued injured mitochondria. Especially, we found that the electroacupuncture up-regulated the expression of Nrf2, and promoted phosphorylation of Nrf2 and nuclear translocation, However, Nrf2 inhibitor Brusatol reversed the neuroprotective effect of electroacupuncture. Conclusion Electroacupuncture can alleviate cerebral I/R injury-induced ferroptosis by promoting Nrf2 nuclear translocation. It is expected that these data will provide novel insights into the mechanisms of electroacupuncture protecting against cerebral I/R injury and potential targets underlying ferroptosis in the stroke. Graphical Abstract